THE EFFECT OF BONUS PACK, SHOPPING LIFESTYLE, AND STORE ATMOSPHERE ON IMPULSE BUYING CONSUMERS OF MATAHARI SOLO GRAND MALL - Ulfa Rantelina, Novia; Andiyani, Rini; Dwanita Widodo, Zandra (IJBLE Scientific Publications Community Inc., 2023)
Impulse buying can occur if the store has a good atmosphere that can affect the emotional situation of consumers, so that impulse purchases occur. The store atmosphere is usually used as a tool for the store as a marketing strategy to increase sales of products offered; advertising posters, product placement, music, aroma, cleanliness of the store, and the store environment are factors in the store that can affect shopping behavior in consumers. This study aims to analyze the bonus pack, shopping lifestyle, and store atmosphere for impulse buying consumers. This research method uses survey research—data collection using questionnaires with the Likert scale and data analysis using multiple linear regression. The results of this study showed that the value of the constant 3.829 marked positive, then impulse buying is positive. At the same time, the value of B1 is 0.337 means that if the bonus pack increases, then impulse buying will also increase, assuming the variable shopping lifestyle and store atmosphere is considered fixed, while the value of B2 is 0.276 means that if shopping lifestyle, assuming variable bonus pack and shopping lifestyle are considered fixed. This study concludes that the overall variables affect consumer impulse buying in Matahari Solo Grand mall.